OPTIMALISASI PEMBIAYAAN MUSYARAKAH DALAM PEMBANGUNAN EKONOMI - Permana, Teguh; Puspitaningsih, Andriani; Surianti (Jurnal Riset Rumpun Ilmu Ekonomi, 2022)
This study aims to determine the development of musyarakah financing in Indonesia. The research method used is descriptive method with content analysis or content analysis. Broadly speaking, this writing systematic is more of a narrative nature that collects secondary data from BPS, opinions of experts, journals, books and articles published on the internet related to musyarakah financing in Indonesia. The results of the study show that musharaka financing continues to show increasing growth from year to year. As a form of financing that focuses on the productive sector, musyarakah financing needs to be further increased compared to murabahah financing which focuses on the consumptive sector.